Long-term adverse events after sleeve gastrectomy or gastric bypass: a 7-year nationwide, observational, population-based, cohort study. Issue 10 (October 2019) - Thereaux, Jérémie; Lesuffleur, Thomas; Czernichow, Sébastien; Basdevant, Arnaud; Msika, Simon; Nocca, David; Millat, Bertrand; Fagot-Campagna, Anne
Summary: Background: Concerns are rising about the late adverse events following gastric bypass and sleeve gastrectomy. We aimed to assess, over a 7-year period, the late adverse events after gastric bypass and sleeve gastrectomy compared with matched control groups. Methods: In this nationwide, observational, population-based, cohort study, we used data extracted from the French National Health Insurance (Système National des Données de Santé) database. All patients undergoing gastric bypass or sleeve gastrectomy in France in 2009, except those who had undergone bariatric surgery in the previous 4 years before inclusion, were matched with control patients with obesity in terms of age, sex, BMI category, baseline antidiabetic therapy, and baseline insulin therapy. Exclusion criteria for the control group included cancer, pregnancy, chronic infectious disease, serious acute or chronic disease in 2008–09, or previous (2005–09) or forthcoming (2010–11) bariatric surgery. The incidence rate was calculated for each type of adverse event leading to inpatient hospital admission over a 7-year period; incidence rate ratios (with 95% CIs) were computed to compare the rate of complications among the bariatric surgery and control groups. Risks of complications during follow-up were compared using Cox proportional-hazards regression analyses. Data were analysed according to the intention-to-treat methodology. Findings: From Jan 1, 2009, to Dec 31, 2009, 8966 patients who underwent bariatric surgery (7359 [82%] women; mean age 40·4 years [SD 11·3]) and 8966 matched controls (7359 [82%] women; mean age 40·9 years [11·4]) were included in analyses 4955 (55%) off 8966 patients in the bariatric surgery group had a primary gastric bypass and 4011 (45%) patients had sleeve gastrectomy. With a mean follow-up of 6·8 years (SD 0·2), mortality was lower in the gastric bypass group than in its control group (hazard ratio 0·64 [95% CI 0·52–0·78]; p<0·0001) and in the sleeve gastrectomy group than in its control group (0·38 [0·29–0·50]; p<0·0001). The gastric bypass and sleeve gastrectomy groups had higher risk than did their control groups for invasive gastrointestinal surgery or endoscopy (incidence rate ratio 2·4 [95% CI 2·1–2·7], p<0·0001, for gastric bypass vs control and 1·5 [1·3–1·7], p<0·0001, for sleeve gastrectomy vs control); for gastrointestinal disorders not leading to invasive procedures (1·9 [1·7–2·1]), p<0·0001, for gastric bypass vs control and 1·2 [1·1–1·4], p<0·0001, for sleeve gastrectomy vs control); and for nutritional disorders (4·9 [3·8–6·4], p<0·0001, for gastric bypass vs control and 1·8 [1·3–2·5], p<0·0001, for sleeve gastrectomy vs control). For psychiatric disorders, there was no significant association (1·1 [0·9–1·4], p=0·190, for gastric bypass vs control and 1·1 [0·8–1·3], p=0·645, for sleeve gastrectomy vs control), except for gastric bypass and alcohol dependence (1·8 [1·1–2·8], p=0·0124). Interpretation: Despite lower 7-year mortality, patients undergoing gastric bypass or sleeve gastrectomy had higher risk of hospital admission at least once for late adverse events, except for psychiatric disorders, than did control patients, with a higher risk observed after gastric bypass than with sleeve gastrectomy. Funding: None.